An approximate method for the progressive failure analysis of a composite lattice rectangular plate. Issue 19 (2nd October 2021) - Kim, Yongha; Park, Jungsun
Abstract: This paper defines in-plane displacement functions of a composite lattice rectangular plate, which is assumed to be a Kirchhoff-Love plate. It presents an approximate method based on the continuous model of conducting a progressive failure analysis for predicting material failure and post-failure behavior of the composite lattice rectangular plate with various boundary and load conditions. To define the approximate method, we use the Ritz method and Hashin's failure criteria. The validity of the present method is verified by comparing the results of the finite element analysis. Finally, we perform parametric and sensitivity analyses to investigate the effects of the design parameters on the failure characteristics of the composite lattice rectangular plates based on the present method. The results allow a database to be obtained on the structural characteristics of composite lattice rectangular plates. Consequently, it is concluded that the present method is well suited to progressive failure analysis of composite lattice rectangular plates due to their relative simplicity and computational efficiency.